From Passion to Profit: Women opting for the Entrepreneurial Way in Kerala (International Journal of Food and Nutritional Sciences, 2022)
Women's entrepreneurship boosts a country's economic progress. The country's economic growth is expanding as more women enter the entrepreneurial world. Entrepreneurship and earning activities are viable methods of empowering women. This article examines how women are increasingly turning to entrepreneurship to transform their passions into profits. It investigates the motives, problems, and influence of female entrepreneurs in today's economy using secondary data. It also discusses how government initiatives, societal changes, and successful case studies have encouraged women to start their own businesses. The article finishes with recommendations for empowering women entrepreneurs through inclusive policies and support ecosystems